Satellite monitoring in the implementation of the agricultural development concept in an urbanized environment - Opryshko, O.; Tsytsiurskyi, Y.; Omelchenko, S.; Hluschenko, O. (Energy and Automation, 2025)
Cities, due to their urbanization and human activity, create heat islands that have the potential for agricultural production. Heat emissions contribute to the extension of the growing season, enabling the cultivation of technical crops even on contaminated soils, which are important for bioenergy and biogas production. The technologies for monitoring heat islands using satellites are discussed, which allow the identification of areas with the highest heat emissions. Research in Kyiv showed that the most stable heat emissions occur in the spring-autumn period, when the temperature ranges from 5 to 25°C, which is optimal for plant development. Satellite monitoring technologies not only detect thermal anomalies but also identify optimal locations for green planting that help reduce the negative impact of the urban environment on vegetation. The developed software solution based on satellite data helps track changes in surface temperature and their effect on vegetation, enabling better planning of agricultural production in urban areas. The example of the Lavina shopping and entertainment center in Kyiv revealed stable heat emissions that can be used for the development of urban agriculture. Proposed crops adapted to these conditions can optimize the use of heat for plant cultivation and provide ecological benefits for the city. The conclusions confirm the significant potential of heat islands for the development of urban agriculture, which contributes to improving ecology in megacities and providing local residents with high-quality products.Key words: satellites, heat islands, urban farming